Achievements after Six Years of The International Partnership for Health Informatics Education - Jaspers, M. W. M.; Gardner, R. M.; Gatewood, L. C.; Haux, R.; Schmidt, D.; Wetter, T. (Yearbook of Medical Informatics, 2005)
To inform the medical and health informatics community on the rational, goals, and the achievements of the International Partnership for Health Informatics Education – IPHIE, (IΦE), that was established at six universities in 1999: The University of Amsterdam, the Universities of Heidelberg and Heilbronn, the University of Health Sciences, Medical Informatics and Technology at Innsbruck, the University of Minnesota, and the University of Utah.We elaborate on the overall goals of IΦE and describe the current state of affairs: the activities undertaken and faculty and student experience related to these activities. In addition we outline the lessons we have learned over these past six years and our plans for the future.IΦE seeks to maintain, improve and promote medical and health informatics education through international collaboration of graduate and baccalaureate programs in medical and health informatics. IΦE members first started to collaborate by supporting and encouraging the exchange of talented students and faculty and by establishing joint master classes for honors students. Following the success of these activities, new initiatives were undertaken such as the organization of student workshops at Medical Informatics conferences and a joint course on strategic information management in hospitals in Europe.International partnerships such as IΦE take time to establish, and, if they are to be successful, maintaining leadership continuity is critically important. We are convinced that IΦE promotes professionalism of future medical informatics specialists. There will be a continuing growth of globalization in higher education. It will therefore become increasingly important to offer educational programs with international components.